2017
DOI: 10.1002/pi.5315
|View full text |Cite
|
Sign up to set email alerts
|

Application of metal − organic frameworks

Abstract: The burgeoning field of metal − organic frameworks or porous coordination polymers has received increasing interest in recent years. In the last decade these microporous materials have found several applications including storage and separation of gases, sensors, catalysis and functional materials. In order to better design new metal − organic frameworks and porous coordination polymers with specific functionalities a fundamental issue is to achieve a basic understanding of the relationship between molecular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
118
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(119 citation statements)
references
References 242 publications
(336 reference statements)
0
118
0
1
Order By: Relevance
“…Abstract: Tw on ew zirconium-based metal-organic frameworks with the composition [Zr 6 O 4 (OH) 4 (OAc) 6 (BDC) 3 ] (CAU-26) and [Zr 5 O 4 (OH) 4 (OAc) 4 (BDC) 2 ]( CAU-27) are reported, which were synthesized from acetic acid, ar arely utilized but green and sustainable solvent (BDC 2À :1 ,4benzenedicarboxylate). Structure determination aided by automated electron diffraction tomography revealed that CAU-26 is composed of layers of well-known {Zr 6 O 8 }c lusters interconnected by terephthalate ions.I nc ontrast CAU-27 exhibits at hree-dimensional structure with as of ar unknown type of one-dimensional inorganic building unit (IBU), which can be rationalized as condensed polyhedron-sharing chains of {Zr 6 O 8 }c lusters.C AU-26 occurs as an intermediate of the CAU-27 synthesis and can be isolated easily,w hen reaction temperature and time are decreased.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Abstract: Tw on ew zirconium-based metal-organic frameworks with the composition [Zr 6 O 4 (OH) 4 (OAc) 6 (BDC) 3 ] (CAU-26) and [Zr 5 O 4 (OH) 4 (OAc) 4 (BDC) 2 ]( CAU-27) are reported, which were synthesized from acetic acid, ar arely utilized but green and sustainable solvent (BDC 2À :1 ,4benzenedicarboxylate). Structure determination aided by automated electron diffraction tomography revealed that CAU-26 is composed of layers of well-known {Zr 6 O 8 }c lusters interconnected by terephthalate ions.I nc ontrast CAU-27 exhibits at hree-dimensional structure with as of ar unknown type of one-dimensional inorganic building unit (IBU), which can be rationalized as condensed polyhedron-sharing chains of {Zr 6 O 8 }c lusters.C AU-26 occurs as an intermediate of the CAU-27 synthesis and can be isolated easily,w hen reaction temperature and time are decreased.…”
mentioning
confidence: 99%
“…Thes tability originates from the strong coordination bond between highly charged Zr 4+ ions (strong Lewis acids) and oxygen anions from the ligand molecules (strong Lewis bases) and is in agreement with the HSAB (hard and soft acids and bases) principle. [4] However,amajor drawback is given by the synthesis conditions of zirconium MOFs,since the majority of reaction routes utilize the highly carcinogenic solvent N,N-dimethylformamide (DMF), which tends to decompose under hydrolysis of the amide bond at elevated temperatures or in an catalytic environment (e.g., acids,b ases,m etal ions). [4] However,amajor drawback is given by the synthesis conditions of zirconium MOFs,since the majority of reaction routes utilize the highly carcinogenic solvent N,N-dimethylformamide (DMF), which tends to decompose under hydrolysis of the amide bond at elevated temperatures or in an catalytic environment (e.g., acids,b ases,m etal ions).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the weak interactions employed to direct self‐assembly in artificial systems,, coordination bonds have played a pivotal role, producing many of the most complex and promising materials, with applications in diverse areas such as biological targeting, chemical reactivity, and gas management . The booming field of metal–organic frameworks certainly attests to its importance . Although the metal ions play a central role in defining the self‐assembly outcome both in terms of geometry and robustness, the ligands responsible for holding the metal ions apart at well‐defined distances are also critical in tuning the resulting self‐assembled architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Coordination polymers and metal-organic frameworks attract the unceasing attention of researchers due to their wide range of potential applications [1][2][3][4][5][6]. One of the universal approaches to the construction of metal-organic frameworks uses a combination of metal ions with aromatic dior polycarboxylate donors and rigid or flexible N-donor bitopic ligands [7,8].…”
Section: Introductionmentioning
confidence: 99%